(untitled) (Journal of the Bangladesh Agricultural University, 2014)
The present study was designed to analyze the cost, benefit and profitability of cassava production in selected areas of Sherpur district in Bangladesh. Data were collected by interviewing a representative sample of 100 practicing cassava farmers, taking each 50 sample from traditional farmers of Jhinaigati and commercial cassava farmers of Sreebardi Upazila. Analyses showed that per hectare cost incurred for cassava was BDT 41,417.22 in Jhinaigati whereas BDT 53,642.59 in Sreebardi Upazila. The average return for cassava was BDT 103,297.58 and BDT 159,527.70 in Jhinaigati and Sreebardi Upazila respectively. Average gross margin for cassava was BDT 61,880.36 and BDT 105,885.10 in Jhinaigati and Sreebardi Upazila respectively. Results of the financial analysis indicate that investment in cassava is profitable since BCR was for cassava were 2.49 and 2.99 in Jhinaigati and Sreebardi Upazila respectively. The technical efficiency analysis reveals that technical inefficiency effects presence in cassava production in the study areas. The estimates for the stochastic frontier cost functions parameters imply that as some cost factors, e.g., cost of labor, power tiller, seedlings, fertilizer, and interest on operating capital increased, total production cost increased. Hence, these variables are important determinants of cassava production in the study area. In a nutshell, though the technical inefficiency exists in the cassava production, it is profitable and, therefore, be replicated in other areas of Bangladesh. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21401 J. Bangladesh Agril. Univ. 12(1): 119-126, June 2014